DUAL ORGANISERING, HIERARKI OG FIREDELINGSLOGIK I ANDES: En komparativ tilgang - Hornborg, Alf (Tidsskriftet Antropologi, 1997)
Alf Hornborg: Dual Organization, Hierarchy and the Logic of Quadripartition in Andean Societies. A Comparative Approach A comparative perspective can help to illuminate the quadripartite, ethnic hierarchies of Andean communities by placing them in a wider, South American context. The ethnography of Southern India also provides us with valuable clues for understanding the structure of traditional, Andean hierarchies. The endogamous moiety systems of the Andes can be understood as transformations of exogamous moiety divisions such as those of central Brazil. In both areas, hierarchies of ranked, endogamous strata have been intersected by exogamous dual divisions. The horizontal, ceremonially and spatially more conspicuous moiety divisions would have had the effect of mystifying and neutralizing the vertical dimensions of political and economic stratification, augmenting moiety allegiance to minimize tensions between strata. The recurrent, quadripartite organization of Andean communities appears to harbour a potential for either the symmetric or restricted exchange of exogamous moieties or the asymmetric exchange of more inclusive and hierarchical social systems. Apparently, the dualistic social categories of Andean communities are classificatory grids which can subsume new ethnic elements as they enter the scene. In maintaining an illusion of reciprocity, dual organization may well have facilitated the growth of hierarchical social systems. The obsession with dual organization in the Andes and the central Brazil suggests an attempt to reproduce the basic, structural principles of two-line terminologies (viz. dual opposition, relative age, and gender) through other means than the simple, transitive logic of kin term usage. At the very point where these ordering principles could no longer be maintained in the course of everyday interaction, they proved to be of such profound significance for resisting chaos that they provided templates for the physical construction of social space.